Ultrastructure of Prothrombin and Thrombin Molecules - Riddle, Jeanne M.; Bernstein, Maurice H.; Seegers, Walter H. (Thrombosis and Haemostasis, 1963)
A technic is described for obtaining shadowcast preparations of bovine prothrombin and thrombin molecules. Three products of prothrombin were investigated. Nonchromatographed prothrombin and prothrombin chromatographed on Amberlite IRC-50 were homogeneous and similar in appearance. The mean particle height of IRC-50 prothrombin was less than that of nonchromatographed prothrombin. In contrast, DEAE cellulose prothrombin products were heterogeneous, approximately Vs larger and of a more spherical molecular configuration. The mean particle height of each type of prothrombin preparation was significantly different from the other. Chromatographic procedures rather than increasing the specific activity of prothrombin products were detrimental to the molecule and produced measurable chemical, functional, and morphological modifications.Three thrombin products were also surveyed. In each case the molecules were discrete particles and had a smaller mean particle height than prothrombin. On the basis of the t test, there were no significant differences between the mean particle heights of IRC-50 thrombin, urea treated thrombin and citrate IRC-50 thrombin. There was no indication of dimer or trimer configurations in the thrombin preparations.